Situational analysis of the Karamoja-Turkana/West Pokot-Easter Equatoria Cluster - Chilambe, Pedro Anglaze; Denje, Telvin; Arum, Shadrack; Vyas, Shalika; Jalang’o Anyango, Dorcas; Awola, David; Girvetz, Evan Hartunian; Wamukoya, George (CGIAR Initiative on Climate Resilience, 2022)
This study evaluates the context within the targeted areas in the Horn of Africa, and summarises common investments in these countries in relation to climate adaptation and climate security based on a review of Nationally Determined Contributions. The report also assesses key agreements in the Karamoja-Turkana/Pokot-Eastern Equatoria cluster, identifying the focus priorities of these agreements and suggested interventions with the purpose of informing stakeholders on regional priorities and investments with cross-border benefits. It maps out the various development projects focused on adaptation and mitigation to climate change with the objective of informing stakeholders on work for scale up, collaboration, and reinforcement through the development of a Green Climate Fund proposal for East Africa.